ANDROID-BASED SALES INFORMATION SYSTEM CASE STUDY ON NABILA BAKERY BREAD FACTORY GORONTALO CITY - Olha Musa; Novita Adam (Universitas PGRI Semarang, 2019)
Sales information system is a system designed to simplify the online sales process. Based on research at Roti Nabila Bakery Factory researchers found problems in the Promotion System that only relied on Sales in conducting sales promotions, Ordering system is still recorded in a piece of paper, Calculation of total sales transactions still use calculator tools and Sales Reports are still recorded in a Sales Book so The researcher wants to Design a Sales Information System Application to solve the problems that exist in the research site. This study uses whitebox and blackbox testing. Whitebox testing is testing with trial techniques on program flow, logic structure and program procedures by flowchart mapping, then calculating the number of edges and nodes. Black box testing method focuses on the functional requirements of the software. Therefore black box trials allow software developers to create a set of input conditions that will train all the functional requirements of a program whether it runs as expected or vice versa. Based on the results of examining Whitebox in one of the processes in this system, namely on the Ordering of bread menu with a balanced yield of Cyclometic Complexity (CC) = 4, this system is stated to work well. While the results of the Blackbox system test can run as expected. Keywords: Information System, Sales, Android, php, html and Mysql.